Review of multi‐domain approaches to indoor environmental perception and behaviour. (June 2020) - Schweiker, Marcel; Ampatzi, Eleni; Andargie, Maedot S.; Andersen, Rune Korsholm; Azar, Elie; Barthelmes, Verena M.; Berger, Christiane; Bourikas, Leonidas; Carlucci, Salvatore; Chinazzo, Giorgia; Edappilly, Lakshmi Prabha; Favero, Matteo; et al.
Abstract: Building occupants are continuously exposed to multiple indoor environmental stimuli, including thermal, visual, acoustic, and air quality related factors. Moreover, personal and contextual aspects can be regarded as additional domains influencing occupants' perception and behaviour. The scientific literature in this area typically deals with these multiple stimuli in isolation. In contrast to single-domain research, multi-domain research analyses at least two different domains, for example, visual and thermal. The relatively few literature reviews that have considered multi-domain approaches to indoor-environmental perception and behaviour covered only a few dozen articles each. The present contribution addresses this paucity by reviewing 219 scientific papers on interactions and cross-domain effects that influence occupants' indoor environmental perception and behaviour. The objective of the present review is to highlight motivational backgrounds, key methodologies, and major findings of multi-domain investigations of human perception and behaviour in indoor environments. The in-depth review of these papers provides not only an overview of the state of the art, but also contributes to the identification of existing knowledge gaps in this area and the corresponding need for future research. In particular, many studies use "convenience" variables and samples, there is often a lack of theoretical foundation to studies, and there is little research linking perception to action. Highlights: Building occupants are continuously exposed to multiple indoor environmental stimuli. Personal and contextual aspects are additional domains influencing occupants' perception and behaviour. Scientific literature in this area typically deals with these multiple stimuli in isolation. The present contribution reviews 219 multi-domain papers on occupants' indoor environmental perception and behaviour. Many studies use convenience variables and samples, lack theoretical foundation, and too few link perception to actions.